Mastering Autodesk Revit Architecture 2013 - Read, Phil, 1965- (Autodesk official training guide., 2012)
Learn BIM the Revit Way Revit is Autodesk's industry-leading Building Information Modeling (BIM) software, and this Autodesk Official Training Guide thoroughly covers core Revit topics such as modeling, massing, sustainability, and more. It also brings you up to speed on advanced techniques such as using Revit in the cloud and how to go direct to fabrication. Organized by real-world workflows, this book covers the interface, templates, worksharing, modeling and massing, visualization techniques for different industries, sustainability, roofs and floors, stairs and railing.